Blood pressure as prognostic marker for body condition, cardiovascular, and metabolic diseases in the common marmoset (Callithrix jacchus). Issue 3 (4th May 2016) - Mietsch, Matthias; Baldauf, Katrin; Reitemeier, Susanne; Suchowski, Marcel; Schoon, Heinz‐Adolf; Einspanier, Almuth
Abstract: Background: The increasing life span of Callithrix jacchus in combination with the occurrence of metabolic and age‐dependent diseases requires improved health surveillance for this species. Methods: The health status of 56 marmosets was studied using a non‐invasive blood pressure (BP) device. Age‐, weight‐, and sex‐dependent changes were analyzed. Four animals with striking BP findings had follow‐up exams. Results: Physiological and pathological BP values could be defined. BP positively correlated with age and weight, while no effect of sex could be found. Measurement time for female and older animals was shorter than for male and younger individuals. Further analysis of the suspicious patients revealed renal or hepatic diseases and cardiac alterations. Conclusion: The description of age and weight influences on BP delivers physiological and pathological values for common marmosets. This may contribute to the understanding of aging process and cardiology in this primate species.